Thermochemical energy storage in barium carbonate enhanced by iron(iii) oxide - Williamson, Kyran; Møller, K.T.; D’Angelo, A.M.; Humphries, Terry; Paskevicius, Mark; Buckley, Craig (ROYAL SOC CHEMISTRY, 2023)
Renewable energy requires cost effective and reliable storage to compete with fossil fuels. This study introduces a new reactive carbonate composite (RCC) where Fe2O3 is used to thermodynamically destabilise BaCO3 and reduce its decomposition temperature from 1400 °C to 850 °C, which is more suitable for thermal energy storage applications. Fe2O3 is consumed on heating to form BaFe12O19, which is a stable Fe source for promoting reversible CO2 reactions. Two reversible reaction steps were observed that corresponded to, first, the reaction between β-BaCO3 and BaFe12O19, and second, between γ-BaCO3 and BaFe12O19. The thermodynamic parameters were determined to be ΔH = 199 ± 6 kJ mol−1 of CO2, ΔS = 180 ± 6 J K−1 mol−1 of CO2 and ΔH = 212 ± 6 kJ mol−1 of CO2, ΔS = 185 ± 7 J K−1 mol−1 of CO2, respectively, for the two reactions. Due to the low-cost and high gravimetric and volumetric energy density, the RCC is demonstrated to be a promising candidate for next generation thermal energy storage.